Endoscopic surgery affects the gut microbiota and its metabolism in breast cancer patients - Li, Jingtai; Gao, Fangfang; Li, Runwei; Chen, Zhilin; Chen, Guoping; Fan, Pingming; Du, Guankui (Frontiers in Microbiology, 2025)
BackgroundDespite the advantages of endoscopic surgery in reducing trauma and enhancing recovery for breast cancer patients, its impact on gut microbiota, which is crucial for health and estrogen metabolism, remains unclear. Further investigation is necessary to fully understand this impact and its implications.Materials and methodsBetween June and December 2022, fecal samples were collected from 20 patients who underwent endoscopic surgery. The gut microbiota composition was determined using 16S rRNA sequencing, while the metabolites were analyzed through liquid chromatography-tandem mass spectrometry (LC-MS/MS). Bioinformatics and statistical analyses were employed to identify significant alterations in microbial taxa abundance and to assess intergroup differences. These analyses included t-tests for pairwise comparisons, one-way ANOVA for multiple group comparisons, and chi-square tests for categorical data analysis.ResultsEndoscopic surgery in breast cancer patients subtly changed gut microbiota diversity and composition. Post-surgery, there was a reduction in Lachnospiraceae, Monoglobaceae and Firmicutes to Bacteroides ratios. Shifts in metabolites were also observed, the changed metabolites impacted pathways such as primary bile biosynthesis and Ascorbate and aldarate metabolism, with PE(PGD1/18:1(9Z)) identified as a key differential metabolite that increased post-surgery. Azasetron, tyramine glucuronide, DL-DOPA, phthalide, acetophenazine, aciclovir, creatinine bicarbonate, and 4-oxo-L-proline being associated with distinct bacterial taxa.ConclusionBreast cancer patients undergoing endoscopic surgery experience a shift in their gut microbiota and metabolic profiles. Therefore, postoperative management, with a particular focus on the adjustment of the gut microbiota, is crucial for enhancing patient recovery and health outcomes.